Environment Agency review of methods for determining organic waste biodegradability and municipal waste diversion. - Godley, Andrew R.; Lewin, Kathy; Graham, Adele; Smith, Richard (Aqua Enviro Technology Transfer, 2003)
The Environment Agency is required to regulate the landfilling of biodegradable organic wastes and their diversion from landfilling. Simple, cost effective, reliable and widely applicable methods for the measurement of organic waste and its biodegradability are needed for this activity. A review of such methods was carried out in order to select promising methods for an experimental screening exercise. The review considered both biological and non-biological methods including simple methods that may provide a surrogate measurement of waste biodegradability instead of the time-consuming biological methods. The biological methods selected for further evaluation were the aerobic specific oxygen uptake rate (SOUR) and dynamic respiration index (DRI) tests, and the anaerobic biochemical methane potential (BMP) test. The non-biological methods selected for further evaluation were dry matter (DM), loss on ignition (LOI), total organic carbon (TOC), total nitrogen (TN), water extractable dissolved organic carbon (DOC), BOD and COD, the lignin and cellulose content and the cellulase hydrolysis method. These tests are being evaluated on a wide variety of typical organic materials that might be found in municipal solid waste (MSW) such as newspaper corrugated paper, compost, kitchen waste (vegetable and animal), garden wastes (grass and twigs), nappies, cotton and wool textiles.
Keywords: Waste; Biodegradable; Organic; Compost; DRI; SOUR; BMP; AT4; Landfill; Diversion